1982
DOI: 10.1007/bf00965092
|View full text |Cite
|
Sign up to set email alerts
|

Immunoblot identification of phosphorylated basic proteins of rat and rabbit CNS and PNS myelin: Evidence for four phosphorylated basic proteins and P2 in rat PNS myelin

Abstract: The immunoblot technique permits the visualization of proteins following their separation on acrylamide gels, transfer to cellulose nitrate sheets and subsequent staining with antiserum. We have utilized this technique to demonstrate the presence of four basic proteins in rat PNS myelin with molecular weights of 21K, 18K, 17K, and 14K. Similarly, we demonstrated the presence of two basic proteins in rabbit PNS myelin (molecular weights of 21K and 18K). Exposure of the immunostained cellulose nitrate strips to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
9
0

Year Published

1983
1983
1993
1993

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 23 publications
3
9
0
Order By: Relevance
“…Agrawal and co-workers have also observed the presence of multiple low-molecular-weight MBP-related proteins from rat (Gilbert et al, 1982) and rabbit myelin (Agrawal et al, 1981) that are phosphorylated in vivo; however, the origin and relationships of these protein bands to the four forms of MBP have not yet been established. Figure 3 shows an autoradiogram of the translation products of the reticulocyte lysate stimulated with poly(A)+ mRNA isolated from the brains of various genotypes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Agrawal and co-workers have also observed the presence of multiple low-molecular-weight MBP-related proteins from rat (Gilbert et al, 1982) and rabbit myelin (Agrawal et al, 1981) that are phosphorylated in vivo; however, the origin and relationships of these protein bands to the four forms of MBP have not yet been established. Figure 3 shows an autoradiogram of the translation products of the reticulocyte lysate stimulated with poly(A)+ mRNA isolated from the brains of various genotypes.…”
Section: Resultsmentioning
confidence: 99%
“…Gaithersburg, MD, U.S.A. The reagents used for polyacrylamide gel electrophoresis (PAGE) and the identification of MBP and PLP by the immunoblot technique have been described in detail(Gilbert et al. 1982; …”
mentioning
confidence: 99%
“…Limited enzymatic digestion of isolated IP proteins from PNS and CNS led to closely similar degradation patterns, being most pronounced in the case of IP2 and IPc. Imrnunoblotting revealed that all IP components Biochemical studies on the protein composition of myelin from mammalian species have revealed that certain extrinsic myelin basic proteins are shared by both the central (CNS) and peripheral (PNS) nervous systems (Braun and Brostoff, 1977;Greenfield et al, 1980Greenfield et al, , 1982Gilbert et al, 1982). In contrast, the hydrophobic myelin components proteolipid protein (PLP) in CNS and major glycoprotein (Po) in PNS differ entirely with regard to amino acid composition (Braun and Brostoff, 1977;, molecular weight (Waeh-from trout PNS and CNS myelins reacted with antibodies to trout IP1 (CNS) and bovine Po protein (PNS) whereas antibodies to rat PLP (CNS) were entirely unreactive.…”
mentioning
confidence: 99%
“…46, 525-533 ( 1986). neldt and Linington, 1980;Gilbert et al, 1982), and antigenicity Waehneldt and Jeserich, 1984). In addition to the glycosylated nature of the Po protein (Everly et al, 1973), the presence of a basal lamina and the direct neighborhood of Schwann cell perikaryon and compact myelin (Raine, 1984) have served to distinguish PNS myelination from that of CNS.…”
mentioning
confidence: 99%
“…Myelin basic proteins (MBPs) are phosphoproteins of the central nervous system (CNS) and peripheral nervous system (PNS) myelin [1][2][3][4][5], During development they are synthesized on free ribosomes of myelin forming cells [6]. Following a relatively short transit time between their site of synthesis and site of deposition.…”
Section: Introductionmentioning
confidence: 99%